Assessment of Farmers’ Perception about Crop Residue Burning in Haryana - Choudhary, Anuradha; Kadian, K.S.; Meena, M.S. (Indian Journal of Extension Education, 2021)
The study was conducted in 2019-2020 to assess the perception of the farmers on crop residue burning (CRB) in Haryana. A total of 180 farmers from three purposively selected districts, namely Karnal, Kurukshetra, and Fatehabad from Haryana, were chosen to collect data. Stratified random sampling was employed in the selection of blocks, villages, and respondents. For measuring farmersâ€™ perception, a scale was constructed using Likertâ€™s method of summated ratings. Farmers perceived CRB as an economical and viable option and considered it an efficient practice. Most farmers did not perceive the happy seeder as feasible since it needed a high horsepower tractor. Farmers’ perception was positively and significantly correlated with education, operational land holding, and annual income (P<0.05). Hence, there is a need to promote community-based approaches like custom hiring centre, bio-mass-based power plants, mushroom cultivation, etc., through extension and advisory services. It may lead to adopting alternative crop residue management options and mitigating residue burning in the long run.